A Bibliometric Analysis and Visualisation of Research Trends in Cobalt-Based Orthopaedic Implants - Singh, Sandeep (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cobalt is one of the widely used metal for orthopaedic implants. The bibliometric analysis had been conducted to understand the active authors, organizations, journals, and countries involved in the research domain of “Cobalt-based orthopaedic implants”. All published articles related to “Cobalt-based orthopaedic implants” from “Scopus”, were analyzed using the VOS viewer to develop analysis tables and visualization maps. This article had set the objective to consolidate the scientific literature regarding “Cobalt-based orthopaedic implants” and also to find out the trends related to the same. The most active journals in this research domain were the Journal of Orthopaedic Research. The most active country was the United States of America. The leading organization engaged in research regarding Cobalt-based orthopaedic implants was the Rush University Medical Center, United States of America. The most active authors were Hallab N.J.